Fabrication and evaluation of a spatially resolved fiber-optic probe for diffuse reflectance measurement for noninvasive diabetic foot ulcer diagnosis perspective - Kumar, Ajay; Hattale, Gangadhar; Pawar, Dnyandeo; Kanawade, Rajesh (Optical Engineering, 2024)
Timely diagnosis and monitoring of wound progression or healing are key to improving the long-term outcome of diabetic foot ulcers (DFU). Diffuse reflectance spectroscopy (DRS) has the potential to noninvasively diagnose the DFU in real time, as it detects changes in local blood volume fraction and oxygenation state level that occur when tissue becomes diseased or ulcerated. Since foot soles have a thicker epidermis and deeper blood vessels/capillaries than other parts of the body, a spatially resolved fiber-optic probe (SRFP) is needed to detect the optimal spatially resolved diffuse reflectance (SRDR) signal from the local site of the ulcer for DFU diagnosis. Therefore, herein, an SRFP consisting of a linear array of seven 400-mu m fibers with detector-source (D-S) fiber separation (rho) ranging from 0.8 to 4.8 mm was designed, fabricated, tested, and evaluated for SRDR measurement from a standard reflectance plate of barium sulfate (BaSO4) and foot sole of 27 healthy human subjects. The variation in SRDR spectra for each detector and source fiber pair measured with BaSO4 was found to be less than 1.6%. In-vivo measurements from the foot sole demonstrate that the fabricated probe has the ability to spatially resolve and distinguish the SRDR spectra from sites, namely, the fifth metatarsal, ball of great joint, calcaneum, and great toe. Experimentally and theoretically, the detector and source fiber pair of rho=1.6 and 2.4 mm were optimal for SRDR measurements from a human foot. To evaluate and validate the performance of SRFP in a context relevant to DFU diagnosis, further SRDS measurements were performed on the solid tissue phantoms that mimic the optical properties of the normal and diabetic foot sole, and their results are statistically found different. Preliminary results suggest that developed SRFP can be explored for DRS measurement from foot ulcer patients to confirm its potential clinical applicability.
Keywords: diabetic foot ulcer; diffuse reflectance spectroscopy; foot sole; spatially resolved fiber-optic probe; tissue phantom

Normal and diabetic foot sole skin mimicking tissue phantom fulfillment for spectroscopic-based DFU diagnostics perspective - Kumar, Ajay; Hattale, Gangadhar; Hinge, Sarika; Kulkarni, Gauri; Late, Dattatray J.; Kanawade, Rajesh (AIP ADVANCES, 2024)
Keywords: OPTICAL-PROPERTIES; STATE

Optimisation of metallic bismuth nanoparticle supported Pt-Bi(x%)/C hybrid electrocatalyst for cost effective and efficient hydrogen production in alkaline media - Dokhe, Revati; Ugale, Atul; Dube, Onkar; Varpe, Vaibhav; Galave, Chaitanya; Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Kumar, Ajay; Husale, Sudhir; Natu, Varun; Shevate, Rahul; et al. (International Journal of Hydrogen Energy, 2025)
The present study employed a simple mechanochemical method followed by 24-h ultrasonication to synthesize oxide-free metallic bismuth (Bi) nanoparticles. This was further used to synthesize a Pt-Bi(x%)/C (NC-x) hybrid electrocatalyst for the hydrogen evolution reaction in alkaline media. X-ray photoelectron spectroscopy and contact angle measurements reveal, Bi modifies the electronic structure and surface morphology of the Pt/C electrocatalyst, thus enhancing reaction kinetics and active site availability. The relative three-electrode study reveals that optimised NC-20 electrocatalyst reduces the overpotentials by 10.44 % and enhances the current density by 53 % compared to commercial Pt/C. The practical applicability of the NC-20 electrocatalyst was studied with the 13 cm2 single cell anion exchange membrane electrolyser. The catalyst demonstrates promising performance where the current density of NC-20//IrO2 relatively increases by 22.6 % compared to standard Pt/ C//IrO2, and shows continuous production and stable performance when monitored for 30 h.
Keywords: AEM; Bismuth nanoparticles; electrocatalyst; Full cell electrolysis; hydrogen evolution reaction; water electrolysis

Photoluminescence decay lifetime study of hydrothermally synthesized highly porous ruthenium-silica composite for optical dissolved oxygen sensing application - Hattale, Gangadhar; Kadam, Rutuja; Virole, Vishal; Pandya, Rinu; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Vanka, Kumar; Saha, Avishek; Kanawade, Rajesh (ACS Applied Nano Materials, 2026)
Pore size and surface area of photoluminescence (PL)-based transition metal composites play crucial roles in facilitating oxygen diffusion, thereby enhancing the response and sensitivity of optical dissolved oxygen (DO) sensors. In this study, we successfully applied the hydrothermal method to synthesize a porous ruthenium composite embedded in a silica matrix, demonstrating its effectiveness for optical DO sensing applications. The ruthenium-silica (Ru-Si) composites were synthesized using Ru(bpy)3 2+ and tetraethyl orthosilicate (TEOS) as precursors, with reaction temperatures ranging from 120 degrees C to 200 degrees C over a fixed duration of 4 h. The structural, morphological, and compositional characterization techniques confirmed the successful synthesis and evaluated the porosity, surface features, and chemical structure of the resulting composites. The optimized Ru-Si composite exhibited the highest porosity, characterized by a specific surface area of 996.78 m2 g- 1, and exhibited the highest decay lifetime of 8.14 mu s in deionized (DI) water, compared to other composites. Importantly, we demonstrate an excellent linear response of the synthesized Ru-Si composite to DO concentrations ranging from 2.58 to 11.16 mg L-1, with a Stern-Volmer constant of 0.12. Furthermore, a density functional theory study was conducted to investigate the electronic transitions and to elucidate the oxygen quenching mechanism of the excited Ru composite with molecular oxygen. The calculated photophysical parameters of the composite show good agreement with the experimental results. Preliminary results suggest that the synthesized Ru-Si with high pore size and surface area could be an efficient and effective composite for use in DO sensing applications.
Keywords: Hydrothermal method; opticalDO sensor; oxygen quenching; photoluminescent; ruthenium composite

Polysulfone-based polymer carbon dot membrane for optical dissolved oxygen sensing application - Kadam, Rutuja; Hattale, Gangadhar; Virole, Vishal; Pal, Sanjivani; Abraham, Athira; Paul, Aditya; Kumar, Ajay; Shevate, Rahul; Banpurkar, Arun; Kanawade, Rajesh; Saha, Avishek (Chemistry-An Asian Journal, 2026)
The precise monitoring of dissolved oxygen (DO) is essential across industrial, environmental, and biomedical applications. However, the state-of-the-art DO sensing methods often suffer from inherent limitations, which hinder their effectiveness for real-time and long-term DO monitoring. Optical DO sensing, despite its advantages, utilizes expensive metal complexes and is prone to photobleaching and slow response time. Here, we introduce a novel polymer carbon dot (PCD) as a promising candidate for lifetime-based optical DO sensing. The PCD is a metal-free, nontoxic, fluorescent, long decay-lifetime material that is synthesized through hydrothermal method. Our fluorescent PCD exhibits high emission quantum yield (24.32%), long decay-lifetime (10.43 & micro;s), and a linear response to DO concentrations ranging from 0.7 to 12.7 mg/L, with a Stern-Volmer constant of 0.1115. Further, to obtain better oxygen diffusion, high porosity, optical transparency, and high flexibility, PCD was embedded into a polysulfone matrix (PSF_PCD). The PSF_PCD membrane shows better results for the decay lifetime (9.4 & micro;s), surface energy (40.26 mN/m), and average pore diameter of 5 nm. Hence, the obtained results demonstrate the applicability of the PCD in optical DO sensors for real-time and long-term monitoring of DO levels.
Keywords: decay lifetime; dissolved oxygen; Hydrothermal method; polymer carbon dots; polysulfone-based membrane